Spherical coral-like synovial chondroma within a popliteal cyst: a case report - Mao, Bingyan; Peng, Qi; Li, Jicai; Qin, Zuoquan; Xie, Shenke (Frontiers in Medicine, 2025)
Popliteal cysts are common lesions, primarily characterized by soft tissue swelling, which may occasionally present with calcifications or small osteochondromas, and can rarely lead to restricted movement. We report a case involving a spherical coral-like synovial chondroma located within a popliteal cyst, which caused significant pain and limited the flexion and extension of the knee joint. Notably, the appearance of the synovial chondroma was strikingly similar to that of spherical coral, and its distinctive imaging features are previously unreported in the literature. Following the excision of both the popliteal cyst and the intra-cystic spherical coral-like synovial chondroma, the patient’s range of motion in the knee joint returned to normal. The unusual morphology may arise from constrained growth within the cyst under pressure during joint movement, potentially influenced by the hyperuricemic microenvironment. Clinicians should consider synovial chondromatosis in the differential diagnosis of complex or calcified popliteal cysts.